Peculiarities of UkrRSS-97 and their application at NSC KIPT accelerators - Mazilov, A.V. (Вопросы атомной науки и техники, 2001)
The main principles and peculiarities of the Ukraine’s Radiation Safety Standards (UkrRSS-97) in comparison with RSS-76/87 and IRPC standards are considered and analyzed. The problems of NSC KIPT Acceleration Complex transition to UkrRSS-97 and the way of their settling are discussed.